Documentation, Analysis and Reconstruction of the Paleo-landuse of Wadi Musa with Special Reference to the Nabataean Period: A Geomatic Study based on Archaeological Evidence - Mohammmad Al Farajat; Saad Twaissi; Mahmoud B Al Hasanat; Abdulla Al-Rawabdeh; Hani Al Falahat; Emad Hijazeen; Ekhlas Al Eide (Geological Agency, 2021)
DOI:10.17014/ijog.8.3.427-441Archaeologists and historians throughout time have relied mainly on textual, architectural, and art-historical analyses to understand the historical context of civilizations. This traditional approach has been challenged, however, by the current new practices in archaeological studies, which tend to rely on more scientific methods (e.g. information systems) to understand the wider context of the socio-cultural aspects of past societies. For example, the Nabataean studies, which for more than seventeen decades after the rediscovery of Petra in 1812, are based on the art historical analysis of the rock-cut facades of the the city of Petra. The wider story of the socio-cultural, political, and economic aspects of the Nabataean culture is still not well understood. Just recently archaeological research was undertaken to improve the understanding of the Nabaatean phenomenon from outside Petra. This paper discusses this new attempt to investigate the spatial organization and land use of Wadi Musa during the Nabataean period based on GIS analysis and new archaeological discoveries. Utilizing GIS in discovering historical phenomena provides a new perspective for analysis, whereby structures are treated not as individual archaeological items but rather as a system. This paper also presents a case study that demonstrates the significance of using GIS for historical research by shedding light on the temporal variation of Wadi Musa settlements with special focus on the paleo-landuse of the Nabatean period. The resulting reconstructed map indicates that Wadi Musa was well planned with special zones for elite residents, industry, rural communities, and agriculture. Social segregation/stratification is also well indicated in the plan of the city. The reconstructed map indicates that the strategy for Nabataean land use for Wadi Musa was to use it as a green zone around the city of Gaia.